Basic psychological needs and self-determined motivation as antecedents of female consumers’ voluntary simplistic clothing consumption practices in South Africa - Sonnenberg, Nadine Cynthia (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.